Best mean square approximations by entire functions of finite degree on a straight line and exact values of mean widths of functional classes - Vakarchuk, S. B.; Doronin, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain exact Jackson-type inequalities in the case of the best mean square approximation by entire functions of finite degree $≤ σ$ on a straight line. For classes of functions defined via majorants of averaged smoothness characteristics $Ω_1(f, t ),\; t > 0$, we determine the exact values of the Kolmogorov mean ν-width, linear mean ν-width, and Bernstein mean $ν$-width, $ν > 0$.